Top-Down Prioritization of Salient Items May Produce the So-Called Stimulus-Driven Capture - Benoni, Hanna (Frontiers in Psychology, 2018)
The current study proposes that top-down attentional prioritization of salient items may produce the so-called stimulus-driven capture. To test this proposal, the 'expectation-based paradigm' was designed on the basis of a visual search task. In Experiment 1, a task-irrelevant singleton frame was presented at the same location in 70% of the trials. The target was either presented at chance level within the singleton-location, or away from it. In line with the singleton capture phenomenon, participants were faster in identifying the target when it appeared in the singleton location compared to non-singleton locations. However, leaving out the singleton frame in 30% of the trials led to a similar effect; participants were faster in identifying the target when it appeared in the expected singleton location compared to expected non-singletons locations (a 'quasi-capture' effect). These results suggest that the participants allocated their attention to the expected singleton location, rather than that the singleton itself captured attention. In Experiment 2, the same task-irrelevant color singleton was presented in a random position in 70% of the trials. This color frame was shown as a non-singleton in all of the 30% singleton-absent multicolored trials. A similar facilitation effect was obtained when the target appeared in the expected singleton color frame compared to other frames, in singleton-absent trials as in singleton-present trials. These results further support the idea that instances of singleton capture can be explained by top-down attentional shifts toward singleton-items. Theoretical implications of these results are discussed. Mostly, the study calls to consider the possibility that all sources of attentional control may be represented by a continuous variable of top-down control, including the category of 'physical salience'.